Spirituality Intervention and Outcomes: Corner stone of Holistic Nursing Practice - Mardiyono, Mardiyono; Songwathana, Praneed; Petpichetchian, Wongchan (Nurse Media Journal of Nursing, 2011)
Background: Holistic nursing results in healing the whole person as human being that has interconnectedness of body mind social cultural spiritual aspect.Objective: The purpose of this paper is to examine the effects of Islamic spirituality interventions on health outcomes in nursing.Method: Databases searched for electronic journals and books that were published since 1994 to 2010 were included.Results: Spirituality intervention mainly composes of prayer, recitation of the holy Qur’an, remembrance of Allah, fasting, charity, prophets’ methods, and modified Islamic methods. Thirteen studies found that various outcomes have been highlighted when applied in several areas of nursing, such as stimulating baby’s cognitive ability in maternal nursing, promoting health during eating halal food, fasting, abstinence of alcohol and tobacco consumption, performing regular exercise, reducing anxiety, and pain in medical-surgical nursing. In mental health nursing, six studies explored effects of prayer and religious psychotherapy to enhance happiness and physical health and alleviate anxiety, and depression. Three studies reported Islamic cognitive therapy to alleviate the auditory hallucination, bereavement, and depression. In critical care nursing, three studies employed reciting the holy Qur’an and talqin in end of life care.Conclusion: Although the literature is limited in the amount and quality of spirituality interventions, some evidences have shown as integrative energy in nursing practice to promote health and minimize some symptoms. Spirituality interventions should be performed to acknowledge the high priority in holistic nursing and support interventions.Keywords: spirituality intervention, holistic nursing, Islam